Genetic diversity analysis and phylogeography of Osteochilus spilurus (Cyprinidae: Labeoninae) from Bangka, Belitung, and Kalimantan Islands using Cytochrome b gene - Ardiansyah Kurniawan; Andi Kurniawan; Anik Martinah Hariati; Nia Kurniawan; Teguh W Nugroho; Endang Bidayani; Ahmad F Syarif; Dewa Gede Raka Wiadnya (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kurniawan A, Hariati AM, Kurniawan A, Kurniawan N, Nugroho TW, Bidayani E, Syarif AF, wiadnya DGR. 2022. Genetic diversity analysis and phylogeography of Osteochilus spilurus (Cyprinidae: Labeoninae) from Bangka, Belitung, and Kalimantan Islands using Cytochrome b gene. Biodiversitas 23: 4738-4746. The Sundaland fish species, Osteochilus spilurus is only utilized commercially in the Belitung Islands and has yet to be domesticated. This species can characterize freshwater fish phylogeography because have a minimum of human influence. This study aimed to analyze the genetic diversity and phylogeography of O. spilurus from the Bangka, Belitung, and Kalimantan Islands using Cytochrome b gene. Twenty fish samples were collected from the Sebangau and Kapuas Rivers in Kalimantan, the Lenggang River in Belitung Island, and the Lebak River in Bangka Island. Forward LA-cyp and reverse HA-cyp primers were used for amplification Cytochrome b gene. Mega 10.0 applications were used to construct of the phylogenetic tree. The phylogeographic analysis uses a comparative phylogenetic tree approach with geographical history. The cytochrome b gene showed variations in the nucleotides of O. spilurus from the three islands. Phylogeography of O. spilurus showed that there are two different clades with intraspecific variation according to a geographic area with bootstrap values of 99-100%. One clade contains fish samples from Bangka and Belitung islands, while the other clade comes from Kalimantan island. The formation of the Karimata Strait (between Bangka-Belitung and Kalimantan Islands) and the pattern of paleo rivers are predicted to influence the disparity.